Composição de cachaças obtidas de cinco variedades de cana-de-açúcar e a correlação da presença de dhurrin na cana com carbamato de etila - Cravo, Francielli D'Carlos (2017)
Cachaça is currently the most widely consumed distilled beverage in Brazil, and because it is produced in different localities, each cachaça has the method of production and the cultural and historical characteristics of each region as a differential. Despite being a genuinely Brazilian product and presenting high economic importance, the cachaça production chain in the country is not technologically homogeneous. The standardization of cachaça is essential for meeting the required standards, aiming at increasing sales and enabling growth in exports. One of the major obstacles in exports of cachaça is the presence of ethyl carbamate, a contaminant with a high carcinogenic power. Little is known about the pathways of formation of this compound. It is believed that one of the main precursors for its formation would be the cyanide ion, produced via the enzymatic degradation of the cyanogenic glycosides present in sugarcane. In the present work, the objective was to characterize the cyanogenic dhurrin glycoside in five different sugarcane varieties, using thin layer chromatography (TLC), and to analyze its possible relationship with the formation of ethyl carbamate in cachaça. For each variety of sugarcane, three extracts were prepared: in methyl alcohol, ethyl acetate and hexane. The extracts were submitted to TLC, where the mobile phase that was most adequate for separation was the mixture of methyl alcohol and ehtyl acetate in a 7:3 ratio, and the stationary phase used was silica Gel 60 G 245®. Chromatographic spots were revealed with iodine vapors. All the physical and chemical parameters for the analyzed cachaças produced from the five different varieties of sugar cane and by different production processes were found to lie within the requirements of the Ministry of Livestock and Supply. Although not exceeding the limit, a significant variation in the final concentration of ethyl carbonate was observed for each sample. The chromatographic tests identified equal values for the Rf of the dhurrin standard and for the sugarcane variety SP 83-2847. Similar values for SP 80-3280 and CTC 11 and different for RB 86-7515 and IAC 86-2480 were observed .